Review of agricultural extension in India: Are farmers' information needs being met? - Glendenning, Claire J.; Babu, Suresh Chandra; Asenso-Okyere, Kwadwo (International Food Policy Research Institute, 2010)
Despite a wide range of reform initiatives in agricultural extension in India in the past decades, the coverage of, access to, and quality of information provided to marginalized and poor farmers is uneven. This paper aims to ascertain why farmers are not accessing information and where information gaps exist, despite the variety of extension approaches in India. Using information provision and access as the basis for analysis, the paper reviews some of the major agricultural extension programs in India by considering their ability to provide information and facilitate information sharing and use in farming communities. The review gives a broad overview of the current extension scene in India while providing a synthesis of recent debates and the observations of various authors as well as working groups in the Ministry of Agriculture and the Planning Commission. The paper examines the challenges and constraints of each agricultural extension approach as it attempts to provide farmers with access to information that is relevant to their farm enterprises. As a result of this analysis, opportunities are identified for increasing extension services' effectiveness and efficiency in reaching smallholder farmers. Research gaps are also identified. The review concludes that there is an increasing need to work in partnership and to share knowledge and skills in order to provide locally relevant services that meet the information needs of marginal and smallholder farmers in India.